An FPGA-based Reconfigurable Mesh Many-Core - Giefers, Heiner; Platzner, Marco (IEEE Transactions on Computers)

FPGA Redundancy Configurations: An Automated Design Space Exploration - Anwer, Jahanzeb; Platzner, Marco; Meisner, Sebastian (Reconfigurable Architectures Workshop (RAW))

Echtzeit Klassifikation von sEMG Signalen mit einem low-cost DSP Evaluation Board - Bockhorn, Arne

A computer vision-based approach to high density EMG pattern recognition using structural similarity - Boschmann, Alexander; Platzner, Marco (Proc. MyoElectric Controls Symposium (MEC))

Towards robust HD EMG pattern recognition: Reducing electrode displacement effect using structural similarity - Boschmann, Alexander; Platzner, Marco (Proc. IEEE Int. Conf. Eng. Med. Biolog. (EMBC))

A Generalized Loop Accelerator Implemented as a Coarse-Grained Array - Brand, Marcel

Easy-to-use-on-the-fly binary program acceleration on many-cores - Damschen, Marvin

Lookup Table Partial Reconfiguration for an Evolvable Hardware Classifier System - Glette, Kyrre; Kaufmann, Paul (IEEE Congress on Evolutionary Computation (CEC))

Entwicklung einer codegrößenoptimierten Softwarebibliothek für 8-Bit Mikrocontroller in netzunabhängigen Notleuchten - Hagedorn, Christoph

A hardware/software infrastructure for performance monitoring on LEON3 multicore platforms - Ho, Nam; Kaufmann, Paul; Platzner, Marco (24th Intl. Conf. on Field Programmable Logic and Applications (FPL))
Keywords: Linux; hardware-software codesign; multiprocessing systems; parallel processing; LEON3 multicore platform; Linux kernel; PMU; hardware counters; hardware-software infrastructure; high performance embedded computing; perf_event; performance monitoring unit; Computer architecture; Hardware; Monitoring; Phasor measurement units; Radiation detectors; Registers; Software

Towards self-adaptive caches: A run-time reconfigurable multi-core infrastructure - Ho, Nam; Kaufmann, Paul; Platzner, Marco (2014 IEEE Intl. Conf. on Evolvable Systems (ICES))
Keywords: Linux; cache storage; embedded systems; granular computing; multiprocessing systems; reconfigurable architectures; Leon3 SPARe processor; custom logic events; evolvable-self-adaptable processor cache; fine granular profiling; integer unit events; measurement infrastructure; microarchitectural events; multicore embedded system; perf_event standard Linux performance measurement interface; processor properties; run-time reconfigurable memory-to-cache address mapping engine; run-time reconfigurable multicore infrastructure; split-level caching; Field programmable gate arrays; Frequency locked loops; Irrigation; Phasor measurement units; Registers; Weaving

EMG-basierte simultane und proportionale Online-Steuerung einer virtuellen Prothese - König, Fabian

Hardware Acceleration of Mechatronic Controllers on a Zynq Platform FPGA - Koch, Benjamin

Advanced AES-key recovery from decayed RAM using multi-threading and FPGAs - Mittendorf, Robert

The Xilinx Zynq Architecture as a Platform for Reconfigurable Heterogeneous Multi-Cores - Rüthing, Christoph

Parallel Monte-Carlo Tree Search for HPC Systems and its Application to Computer Go - Schäfers, Lars
Monte-Carlo Tree Search (MCTS) is a class of simulation-based search algorithms. It brought about great success in the past few years regarding the evaluation of deterministic two-player games such as the Asian board game Go. In this thesis, we present a parallelization of the most popular MCTS variant for large HPC compute clusters that efficiently shares a single game tree representation in a distributed memory environment and scales up to 128 compute nodes and 2048 cores. It is hereby one of the most powerful MCTS parallelizations to date. In order to measure the impact of our parallelization on the search quality and remain comparable to the most advanced MCTS implementations to date, we implemented it in a state-of-the-art Go engine Gomorra, making it competitive with the strongest Go programs in the world. We further present an empirical comparison of different Bayesian ranking systems when being used for predicting expert moves for the game of Go and introduce a novel technique for automated detection and analysis of evaluation uncertainties that show up during MCTS searches.

Optimizing the Generator Start-up Sequence After a Power System Blackout - Shen, Cong; Kaufmann, Paul; Braun, Martin (IEEE Power and Energy Society General Meeting (IEEE GM))

A New Distribution Network Reconfiguration and Restoration Path Selection Algorithm - Shen, Cong; Kaufmann, Paul; Braun, Martin (Power Systems Computation Conference (PSCC))

Multithreaded Parallelization of Mechatronic Controllers on a Zynq Platform FPGA - Surmund, Sebastian

Applications of Evolutionary Computation - 17th European Conference, EvoApplications - I. Esparcia-Alcázar, Anna; Eiben, A.E.; Agapitos, Alexandros; Simões, Anabela; G.B. Tettamanzi, Andrea; Della Cioppa, Antonio; M. Mora, Antonio; Cotta, Carlos; Tarantino, Ernesto; Haasdijk, Evert; Divina, Federico; Fernández de Vega, Francisco; et al.

Analytic reliability evaluation for fault-tolerant circuit structures on FPGAs - Anwer, Jahanzeb; Platzner, Marco (IEEE International Symposium on Defect and Fault Tolerance in VLSI and Nanotechnology Systems (DFT))

Fast process variation analysis in nano-scaled technologies using column-wise sparse parameter selection - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; Yazdani, Majid; De Micheli, Giovanni (2014 IEEE/ACM International Symposium on Nanoscale Architectures (NANOARCH))

Adaptive load allocation for combining Anomaly Detectors using controlled skips - Berger, Mario; Erlacher, Felix; Sommer, Christoph; Dressler, Falko (2014 International Conference on Computing, Networking and Communications (ICNC))

Towards an Open Source IEEE 802.11p stack: A full SDR-based transceiver in GNU Radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Timings matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (Proceedings of the 9th ACM international workshop on Wireless network testbeds, experimental evaluation and characterization - WiNTECH '14)

Towards a vehicular cloud - using parked vehicles as a temporary network and storage infrastructure - Dressler, Falko; Handle, Philipp; Sommer, Christoph (Proceedings of the 2014 ACM international workshop on Wireless and mobile technologies for smart cities - WiMobCity '14)

Towards a simulation framework for paraglider networks - Eckert, Juergen; Sommer, Christoph; Eckhoff, David (Proceedings of the 11th ACM symposium on Performance evaluation of wireless ad hoc, sensor, & ubiquitous networks - PE-WASUN '14)

SmartRevoc: An efficient and privacy preserving revocation system using parked vehicles - Eckhoff, David; Dressler, Falko; Sommer, Christoph (38th Annual IEEE Conference on Local Computer Networks)

Driving for Big Data? Privacy Concerns in Vehicular Networking - Eckhoff, David; Sommer, Christoph (IEEE Security & Privacy)

On the impact of street width on 5.9 GHz radio signal propagation in vehicular networks - Erlacher, Felix; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2014 11th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

The Role of Parked Cars in Content Downloading for Vehicular Networks - Malandrino, Francesco; Casetti, Claudio; Chiasserini, Carla-Fabiana; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Short paper: Vehicle shadowing distribution depends on vehicle type: Results of an experimental study - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Lo Cigno, Renato; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Towards energy efficient smart phone applications: Energy models for offloading tasks into the cloud - Segata, Michele; Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2014 IEEE International Conference on Communications (ICC))

A networking perspective on self-organizing intersection management - Sommer, Christoph; Hagenauer, Florian; Dressler, Falko (2014 IEEE World Forum on Internet of Things (WF-IoT))

A cluster based architecture for intersection collision avoidance using heterogeneous networks - Tung, Lung-Chih; Mena, Jorge; Gerla, Mario; Sommer, Christoph (2013 12th Annual Mediterranean Ad Hoc Networking Workshop (MED-HOC-NET))

What influences dwell time during source code reading?: analysis of element type and frequency as factors - Busjahn, Teresa; Bednarik, Roman; Schulte, Carsten (ETRA)

Eye tracking in computing education - Busjahn, Teresa; Schulte, Carsten; Sharif, Bonita; Begel, Andrew; Hansen, Michael; Bednarik, Roman; Orlov, Paul; Ihantola, Petri; Shchekotova, Galina; Antropova, Maria (ICER)

Developing Coding Schemes for Program Comprehension using Eye Movements - Busjahn, Teresa; Schulte, Carsten; Kropp, Edna (PPIG)

Proceedings of the 9th Workshop in Primary and Secondary Computing Education, WiPSCE 2014, Berlin, Germany, November 5-7, 2014

RESOLVE: An Emotion Word Suggestion System Facilitates Language Learners’ Emotional Expressions - Chen, Mei-Hua; Chen, Wei-Fan; Ku, Lun-Wei (Proceedings of the AsiaCALL 2014)

Difference Computation for Grammar-Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Thiele, Sebastian (Proceedings of the Second Australasian Web Conference)

Keyword Search on DAG-Compressed XML Data - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (Proceedings of the Second Australasian Web Conference)

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Preference-based learning of ideal solutions in TOPSIS-like decision models - Agarwal, M.; Fallah Tehrani, A.; Hüllermeier, Eyke (Journal of Multi-Criteria Decision Analysis)

Extended graph-based models for enhanced similarity search in Cabase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Transactions of Computational Biology and Bioinformatics)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Visualization of evolving fuzzy-rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Preference-based reinforcement learning: evolutionary direct policy search using a preference-based racing algorithm. - Busa-Fekete, Robert; Szörenyi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, A.; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.M.; Hüllermeier, Eyke (Neurocomputing)